Thermodynamic and spectroscopic study on the binding of interaction anionic phthalocyanine with calf thymus DNA. Issue 6 (2011) - Dezhampanah Dezhampanah, Hamid Hamid; Darvishzad Darvishzad, Termeh Termeh; Aghazadeh Aghazadeh, Mehrnaz Mehrnaz
Abstract : The interaction between anionic form of copper (II) N, N', N", N'"-tetrasulfonated phthalocyanine Cu (tspc) and to calf thymus deoxyribonucleic acid (ct-DNA) is investigated by measuring UV-vis absorption and fluorescence spectroscopy in phosphate buffer. The binding constant and stoichiometry were determined by analysis of optical absorption spectra of phthalocyanine at various ct-DNA concentrations using SQUAD software. The static mode of fluorescence quenching of phthalocyanine by calf thymus deoxyribonucleic acid indicates the formation of a ground-state complex. The formation of ground-state complex is a spontaneous molecular interaction procedure in which outside groove binding through the formation of an axial bond between the base pairs of nucleotide and Cu in the central core of phthalocyanine.